Steatohepatitic hepatocellular carcinoma: imaging findings with clinicopathological correlation. Issue 2 (February 2021) - Inui, S.; Kondo, H.; Tanahashi, Y.; Fukukura, Y.; Sano, K.; Morisaka, H.; Saito, K.; Kondo, F.; Fukusato, T.; Furui, S.; Oba, H.
Abstract : AIM: To evaluate the clinicopathological and computed tomography (CT) and magnetic resonance imaging (MRI) findings of steatohepatitic hepatocellular carcinoma (SH-HCC). MATERIALS AND METHODS: Clinicopathological and radiological features were evaluated in 20 patients with SH-HCC. The diagnosis of SH-HCC was made histologically if the tumour had four of the following five characteristics: steatosis (>5% tumour cells), ballooning, Mallory–Denk bodies, interstitial fibrosis, and inflammation. All patients underwent dynamic CT and MRI. CT and MRI images were reviewed for morphological features including tumour size, presence, and distribution of fat, and patterns and degree of contrast enhancement. RESULTS: Obesity, hypertension, and history of heavy alcohol intake were common clinical findings observed in 10 (50%), 13 (65%), and 11 (55%) of the 20 patients, respectively. Steatosis and steatohepatitis were pronounced in the background liver in 12 (60%) and 10 (50%) patients, respectively. SH-HCC was moderately differentiated in 18 patients (90%) and well differentiated in two (10%). Pathologically, steatohepatitic features were diffuse in 12 (60%) of the 20 tumours and focal in eight (40%). Tumour size and the percentage of intratumoural steatosis were not correlated ( r= 0.17, p= 0.47). On CT, 16 (80%) patients showed arterial phase enhancement and delayed washout. On MRI, 16 (80%) of 20 tumours showed prominent fatty deposition (10 diffusely, six focally) with arterial phase enhancement. CONCLUSIONS: SH-HCC is likely to show prominent fatty deposits with arterial phase enhancement on CT and MRI. A hypervascular lesion with prominent fatty change should raise the diagnostic suspicion of SH-HCC. Highlights: Pathologically, steatohepatitic hepatocellular carcinoma (SH-HCC) was mostly moderately differentiated with fatty deposition. Steatohepatitic hepatocellular carcinoma showed prominent fatty deposits along with arterial phase enhancement on CT and MRI. A hypervascular lesion with prominent fatty change should raise the diagnostic suspicion of SH-HCC.